HIGHER EDUCATION IN THE PERCEPTION OF RUSSIAN-SPEAKING USERS (On the example of search queries of Yandex) - Victoria L. Silaeva (Высшее образование в России)
The article considers search queries related to higher education. This method of investigation is based on the statistics of search engines fixing the form of requests for different keywords. Russian-speaking Internet users form a semantic field of «higher education », and we know it having identifications of the most demanded inquiries. Some trends of higher education come to light. Dissatisfaction with higher education was revealed among users, higher education is more associated with a diploma which can be bought. And this is second higher education what improves inefficient higher education. By means of additional search queries the authentic Internet rating of universities, faculties, chairs comes to light. Search queries also state transformation of various written forms of knowledge control in higher education in a commercial product. Recommendations about further use of a method of the analysis of search queries are made at the end of the article.